Mosquito adulticides: what are they and how are they registered? - Steinke, T. L., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes what adulticides are, and how they are registered nationally and in the state of Colorado.
Adult mosquito control products
CEPEP 11/04, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Mosquitoes -- Control; Mosquitoes -- Control -- Colorado; Pesticides -- Environmental aspects; Pesticides -- Environmental aspects -- Colorado